(untitled) (Tribhuvan University Journal of Microbiology, 2018)
Objectives: The purpose of this study was to characterize the indigenous Bacillus thuringiensis (Bt) isolated from the soil samples of central development region of Terai. Methods: A total of 50 soil samples collected from cultivated and barren fields of Terai region. Isolation was carried out using the acetate selection protocol as described by (Russell and Al 1987) with a slight modification. The Nutrient broth (NB) was acetated by using 0.25M sodium acetate which is a selective enrichment method for isolation of Bt. Characterization of the isolate was done by phenotyping methods (microscopy and biochemical). Results: No distinct variation was observed between the isolates of cultivable and uncultivable lands. Bt were categorized into7 different types based on colony morphology. The dominant colony was fried egg type identical with the reference strain, followed by flat white type of colony. The result showed that even though the colony morphology is same but the ICPs (Insecticidal crystal proteins) shapes produced by them vary, rod shapes (53.57%), spherical (10.71%), ovoid (8.3%), amorphous (17.85%), capheaded (9.5%). ICPs morphology reveal the cry1, cry2, cry3, cry4, cry8, cry 9, cry10 and cry11 types of gene may be present in the native isolates. Conclusion: This study represents the first report of several indigenous Bacillus thuringiensis strains with significantly different ICPs producing stains from hot tropical climate.